(untitled) (Fiep Bulletin - online, 2012)
The World Summit on Physical Education was the most important event related to Physical Education at the turn of the millennium. The document issued on this major occasion, namely, the Berlin Agenda, has had great influence on virtually every action that took place in the field of Physical Education since then.The most relevant points on this Agenda were related to the wide scope of Physical Education along people’s lives, especially among children, and to everyone’s right to Physical Education.Having attended this event, and having engaged in the resolutions of the Berlin Agenda (ICSSPE), FIEP once again published a Physical Education World Manifesto - FIEP 2000, deeply influenced by the conclusions stated in the Berlin event. This inspiration was clearly effective in Chapter I (Everyone’s right to Physical Education), Chapter II (Concept of Physical Education), Chapter IV (Quality in Physical Education), Chapter VI (Physical Education for Health), Chapter XVI (Physical Education against Discrimination and Social Exclusion) and article 25 (Role played by Physical Education in current days).Through its publication, which is a contemporary reference in the field, FIEP reaches 124 countries in the whole world. Thus, in fact, FIEP plays its role as one more international institution to spread the ideas approved in the World Summit on Physical Education.